The Use of Red Dragon Fruit Gel as A Disclosing Agent for Plaque Measurement - RR Ratnasari Dyah Purnomowati; Arianto Arianto; Linasari Linasari; Muliadi Muliadi (Dental Therapist Journal, 2024)
Assessing oral hygiene through plaque index assessment is essential to identify areas that require attention, as poor hygiene can lead to problems such as caries, gingivitis, periodontitis and systemic health issues. In response to challenges such as limited access to natural tooth colouring materials and the side effects of chemical alternatives, red dragon fruit has emerged as a safe and natural option. This experimental study aimed to develop a red dragon fruit disclosing gel with concentrations of 35%, 50%, and 75% and to compare the staining effectiveness of these three concentrations. The study employed an experimental research design categorized as an "experimental study" using the Posttest Only Design. In this design, interventions (X) are carried out, followed by posttest measurements (O2). Since there is no control group, the results of O2 cannot be compared with other groups. This approach is also referred to as the "One-Shot Study." The observations (O2) provide descriptive data, with parameters measured including color intensity and plaque index scores. The study was conducted on university students as the sample population. The results revealed that a 35% concentration of red dragon fruit gel was effective in disclosing dental plaque by staining it. However, the highest color absorption and most intense staining were observed at the 75% concentration. The study concluded that a 35% concentration of red dragon fruit gel is sufficient for use as a disclosing agent, while the 75% concentration provides the best and most intense staining. Future research is recommended to stabilize the anthocyanin content in red dragon fruit extract by incorporating acetic acid or other stabilizing agents.